Social media and traditional media - Jaime Marques-Pereira (EconPol Forum, 2025)
Social media affects how traditional outlets select and frame news, acting as a feedback tool for journalists. The influence of social media causes outlets to offer more homogeneous reporting and to cover a larger proportion of soft news. Social media has turned citizens into reporters, bringing new perspectives into the realm of information but raising accuracy concerns. Politicians' social media posts are amplified by traditional outlets, shaping news and public opinion. European policy must address how social and traditional media interact to protect pluralism and accountability.
Keywords: 330